Interaction between human-machine interface and avionics on aircraft cockpit - Ismayil Ismayilov (Problems of Information Society, 2022)
The problem of the human factor, the negative impact of which is often associated with the psycho-physiological characteristics of a person, remains a priority in ensuring the safety of flight, as well as the crew in performing aircraft control operations. The study of the proposed approaches, methods and technical tools aimed at reducing the impact of the human factor on flight safety shows the insufficient effectiveness of available methodological tools in eliminating the “suddenly arising” unreliability of aviation personnel. This situation necessitates the development of an aircraft control system, taking into account the characteristics of all its components and the creation of a virtual pilot assistant interacting with the avionics system. The article discusses various aspects of the interaction of the pilot with the avionics system. It presents the concept of creating a virtual assistant to the pilot in his work on board using human-machine interfaces providing the possibility of observation, communication and flight control. The concept of a cognitive pilot-aircraft interface is proposed, which introduces knowledge-based adaptive functionality into the system to help the crew in performing important tasks which are critical in terms of flight safety.